THE MORPHOMETRY AND THE OCCURRENCE OF CERVUS ELAPHUS (MAMMALIA, CERVIDAE) FROM THE LATE PLEISTOCENE OF THE ITALIAN PENINSULA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2015)
The evolutionary trends and adaptations of the red deer from the Middle Pleistocene to the present day are well documented in Eurasia. These are generally explained by the high capability of this deer to adapt to different enviromental and climatic conditions. The large number of subspecies attributed to Cervus elaphus , often limited to specific paleogeographical areas above all during the late Middle Pleistocene, can be explained by this characteristic. The abundant remains of red deer collected from Late Pleistocene and older Holocene fossiliferous localities in Italy has allowed a detailed analysis of morphometric features in different areas of the Italian Peninsula and also some interesting paleoecological discussion. The variation and differences observed in the size of the red deer show close relationships with the latitude and the paleoclimate.